1978
DOI: 10.1172/jci108980
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of the low density lipoprotein receptor. Diminished receptor activity in lymphocytes from heterozygotes with familial hypercholesterolemia.

Abstract: A B S T R A C T Using circulatinig mononuclear cells as a readily available tissue and using the rate of high af: finity degradation of 1251-labeled low density lipoprotein (LDL) as an index of' cell surface LDL receptor activity, we have measured receptor activity in cells from 53 individuals. This group includes 32 healthy suibjects, 15 subjects with the heterozygous forimi of famiiilial hvpercholesterolemia, anid 6 subjects with hyperlipidemic disorders other than familial hypercholesterolemia. 7 of the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(49 citation statements)
references
References 20 publications
4
45
0
Order By: Relevance
“…On many occasions, patients may initially consult a dermatologist. When it is difficult to differentiate homozygous from severe heterozygous FH, it is possible to make a definitive diagnosis based on the detection of reduced LDL receptor activity in fibroblasts/lymphocytes (20% or less of the normal activity) 58) and LDL-receptor, ApoB or PCSK9 gene mutations.…”
Section: Diagnosis Of Homozygous Fhmentioning
confidence: 99%
“…On many occasions, patients may initially consult a dermatologist. When it is difficult to differentiate homozygous from severe heterozygous FH, it is possible to make a definitive diagnosis based on the detection of reduced LDL receptor activity in fibroblasts/lymphocytes (20% or less of the normal activity) 58) and LDL-receptor, ApoB or PCSK9 gene mutations.…”
Section: Diagnosis Of Homozygous Fhmentioning
confidence: 99%
“…2). Brown and Goldstein and co-workers, who obtained similar results with both fibroblasts and lymphocytes (3)(4)(5), have designated the more concentration-sensitive part of the curve "high-affinity" degradation and the less concentration-sensitive part "low-affinity" degradation (5). The differences in LDL degradation between cells from heterozygotes on or not on colestipol were more marked at higher LDL concentrations ( Fig.…”
Section: Methodsmentioning
confidence: 93%
“…After preincubation in LPDS, the contents of the flasks for each subject were pooled, leaving behind monocytes, which adhered to the sides of the flask (4). Differential counts of stained smears showed that the preincubated cell preparations contained less than 1% monocytes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of IHI-Iabelled human LDL by freshly isolated blood mononuclear cells was measured as described by Bilheimer et 01. 3 Plant sterols in plasma were quantitated by gas chromatography (GC) after hydrolysis and extraction." Coprostanol (Steraloids Ltd, Croydon, UK) was used as the internal standard and taken through the complete procedure.…”
Section: Xanthomata Of the Achilles Tendons (A Bj And Extensor Tendomentioning
confidence: 99%